How informed Receivers are influences the effect of Bayesian Persuasion: An example of Bank run - Jiao, Letian; Zhang, Luyao; Chen, Haitao (International journal of Engineering, Business and Management, 2021)
This paper considers Bayesian persuasion game when receivers are partially informed andtheir behaviors influence each other. Receivers get signal independent of sender. And sender is fully informed about the state and signal receivers get. Sender sets a persuasion rule to give recommendation to receivers which plays role in communicating information of state and prompting cooperation between receivers.